Exercise and brain health in patients with coronary artery disease: study protocol for the HEART-BRAIN randomized controlled trial - Toval, Angel; Solis-Urra, Patricio; Bakker, Esmée A.; Sánchez-Aranda, Lucía; Fernández-Ortega, Javier; Prieto, Carlos; Alonso-Cuenca, Rosa María; González-García, Alberto; Martín-Fuentes, Isabel; Fernandez-Gamez, Beatriz; Olvera-Rojas, Marcos; Coca-Pulido, Andrea; et al. (Frontiers in Aging Neuroscience, 2024)
Introduction: Patients with coronary artery disease (CAD) have a higher risk of developing cognitive impairment and mental health disorders compared to the general population. Physical exercise might improve their brain health. The overall goal of the HEART-BRAIN randomized controlled trial (RCT) is to investigate the effects of different types of exercise on brain health outcomes in patients with CAD, and the underlying mechanisms. Methods: This three-arm, single-blinded RCT will include 90 patients with CAD (50-75 years). Participants will be randomized into: 1) control group - usual care (n=30), 2) aerobic high-intensity interval training (HIIT) (n=30), or 3) HIIT combined with resistance exercise training (n=30). The 12-week intervention includes 3 supervised sessions (45-min each) per week for the exercise groups. Outcomes will be assessed at baseline and post-intervention. The primary outcome is to determine changes in cerebral blood flow assessed by magnetic resonance imaging. Secondary outcomes include changes in brain vascularization, cognitive measures (i.e., general cognition, executive function and episodic memory), and cardiorespiratory fitness. Additional health-related outcomes, and several potential mediators and moderators will be investigated (i.e., brain structure and function, cardiovascular and brain-based biomarkers, hemodynamics, physical function, body composition, mental health, and lifestyle behavior). Conclusions: The HEART-BRAIN RCT will provide novel insights on how exercise can impact brain health in patients with CAD and the potential mechanisms explaining the heart-brain connection, such as changes in cerebral blood flow. The results may have important clinical implications by increasing the evidence on the effectiveness of exercise-based strategies to delay cognitive decline in this high-risk population.